(untitled) (Journal of the College of Basic Education, 2022)
Not only the sense of beauty and taste of the mere hope of nature, but also through an integrated system and standards and forms and symbols and buildings and interactive drawings and behavior, in order to refine the student’s personality in all aspects of mental, psychological, social and physical ... Etc .. Also to increase aesthetic awareness, aesthetic taste, Aesthetics in order to prepare a promising generation to interact with life in a positive and taste that helps creativity and innovation.As social anxiety is a widespread psychological disease, it has become a remarkable phenomenon in the present age due to the complex and difficult circumstances that the student experiences in particular. It requires him to perform various social roles to satisfy his needs with success and excellence in order to achieve the highest levels of utilization and development To community requirements. The art plays a major role in the student’s life, which serves as a main language through which ideas and feelings are transferred to the outside world. Freud has conducted studies on the nature of art and its ability to embrace its psychological feelings directly related to the subconscious. In order to find solutions to psychological and social problems using the arts as a method of treatment, whether psychologically or socially. (Yami, 2000, p. 10) In this sense, the art education is concerned with social anxiety as a manifestation of the behavior that relates to the aesthetic response. Therefore, the present study came in an attempt to answer the following question? What is the relationship between aesthetic response and social anxiety among middle school students? In order to achieve the research objectives, the researcher put the following zero hypothesis:- There was no significant correlation between (0.05) between the aesthetic response and the social anxiety among students in the preparatory stage.The researcher used two tools: the aesthetic response scale and the Hijazi scale for social anxiety. The two measures were applied to the sample and the researcher obtained the following result: - There is no relationship between aesthetic response and social anxietyThe researcher recommended: the allocation of hours of guidance in which the dialogue and educational and psychological discussion directly to know the concerns and suffering of students, and work to broadcast the spirit of hope and optimism in them. It also suggested conducting a study on aesthetic response and its relation to artistic expression among middle school students